INDIRECT TRANSLATION OF FIGURATIVE LANGUAGE IN DAILY LIFE AND OBJECT IMAGERY IN REMARQUE’S DER WEG ZURÜCK: A COMPARATIVE STUDY IN RUSSIAN AND UZBEK TRANSLATIONS (International Conference on Education, Psychology and Humanities, 2026)
This study examines how figurative language depicting everyday objects in Erich Maria Remarque’s novel Der Weg zurück is translated into Russian and Uzbek, focusing on the effects of indirect (relay) translation on stylistic nuance. The novel’s ordinary items – chairs, clothing, candles, mirrors, bread, coffee – carry symbolic weight, reflecting postwar trauma, peace, and absurdity in the source texts. We conduct a comparative structural-semantic analysis of selected passages containing metaphors, similes, grotesque imagery, metonymy, irony, hyperbole, and symbolism. By aligning the German source with its Russian translation and the Uzbek re-translation (via Russian), we identify shifts, losses, and substitutions in figurative expressions. The results show that while some stylistic devices (similes, basic symbolism) are preserved across translations, others (metaphors, subtle irony) undergo significant modulation or loss. We interpret these shifts through the lens of translation theory – including Catford’s shifts, Nida’s equivalence, skopos theory (Vermeer) and Nord’s loyalty principle – to understand the influence of linguistic, cultural, and relay factors.
Keywords: Indirect translation; figurative language; stylistic devices; translation shifts; cross-cultural equivalence; postwar literature